Outcomes of monoamniotic twin pregnancies managed primarily in outpatient care—a Danish multicenter study. (17th December 2018) - Madsen, Caroline; Søgaard, Kirsten; Zingenberg, Helle; Jørgensen, Finn S.; Rosbach, Hanne; Hoseth, Eva; Pedersen, Lars H.; Petersen, Olav B.
Abstract: Introduction: Monoamniotic twin pregnancies are high‐risk pregnancies, and management by inpatient or frequent outpatient care is recommended. We report the outcomes of a national cohort of monoamniotic twin pregnancies managed primarily as outpatients. Material and methods: We prospectively analyzed the recorded data from the Danish Fetal Medicine Database, local databases, and medical records of all monoamniotic twin pregnancies diagnosed at the first trimester scan or later, and managed at the six major fetal medicine centers in Denmark over a 10‐year period. Results: Sixty‐one monoamniotic twin pregnancies were included. Thirteen pregnancies were terminated early. Of the remaining 48 pregnancies with a normal first trimester scan, there were 36 fetal losses (25 spontaneous miscarriages <22 +0 weeks, 3 late terminations and 8 intrauterine deaths >22 weeks) and 60 liveborn children (62.5%), all of whom were delivered by cesarean delivery at a median gestational age of 33 +0 weeks. Three children had minor malformations and there was 1 pregnancy with twin‐to‐twin transfusion syndrome. After 26 +0 weeks, 78.8% were managed as outpatients. Intrauterine death occurred in 3.8% of outpatients and in 28.6% of inpatients (admitted due to complications). At weeks 32, 33 and 34, the prospective risk of intrauterine death was 6.9%, 4.2% and 5.9%, respectively. Conclusion: In this nationwide, unselected population, only 62.5% of fetuses with a normal first trimester scan were born alive. In contrast, the mortality was 3.8% after 26 weeks among the 78.8% of the cohort that was managed as outpatients. More knowledge is still needed to predict which pregnancies are at the highest risk of intrauterine death.